Viruses and Gram-negative bacilli dominate the etiology of community-acquired pneumonia in Indonesia, a cohort study - Helmia Farida; M. Hussein Gasem; Agus Suryanto; Monique Keuter; Nasirun Zulkarnain; Bambang Satoto; Annemiek A. van der Eijk; R. Djokomoeljanto; Hendro Wahyono; Henri A. Verbrugh; Juliëtte A. Severin; Peterhans J. van den Broek (International Journal of Infectious Diseases, 2015)
Objective: Knowledge about the etiology of community-acquired pneumonia (CAP) is essential for adequate management. Presently, few studies about CAP are available from Southeast Asia. This study aimed to investigate the etiology, severity, and outcome of CAP in the most populous Southeast Asia country, Indonesia. Methods: From October 2007 to April 2009, adult patients admitted with CAP to two hospitals in Semarang, Indonesia, were included to detect the etiology of CAP using a full range of diagnostic methods. The severity of disease was classified according to the Pneumonia Severity Index (PSI). The outcome was assessed as 30-day mortality. Results: In total, 148 consecutive patients with CAP were included. Influenza virus (18%), Klebsiella pneumoniae (14%), and Streptococcus pneumoniae (13%) were the most common agents identified. Other Gram-negative bacilli, Mycobacterium tuberculosis, Chlamydia pneumoniae each accounted for 5%. The bacteria presented wild type antibiotic susceptibility profiles. Forty-four percent of subjects were high-risk patients (PSI class IV-V). The mortality rate (30%) was significantly associated with disease severity score (P<0.001), and with failure to establish an etiological diagnosis (P=0.027). No associations were found between etiology and underlying diseases, PSI class, nor mortality. Conclusions: Viruses and Gram-negative bacilli are dominant causes of CAP in this region, more so than S. pneumoniae. Most of the bacteria have wild type susceptibility to antimicrobial agents. Patients with severe disease and those with unknown etiology have a higher mortality risk.